2007
DOI: 10.1093/eurpub/ckm052
|View full text |Cite
|
Sign up to set email alerts
|

Selective international migration by social position, health behaviour and personality

Abstract: Migrants are self-selected by health behavioural and personality factors, which may compromise their health. The special requirements of migrants should be recognized in health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 24 publications
11
55
2
3
Order By: Relevance
“…This implies that ethnic divides run deep regarding the intentions to study abroad and are not mediated by the other relevant individual level characteristics (including social class/status indicators). Of the "Big Five" personality traits (Model 2), Extraversion and Openness associate positively with the probability of willingness to continue studies abroad, which is in line with previous research (Paulauskaite et al 2010, Silventoinen et al 2008. Of these two personality traits, however, only Openness remains significant after adding various forms of capital in Model 3.…”
Section: Individual-level Characteristics Shaping Intentions To Studysupporting
confidence: 87%
See 1 more Smart Citation
“…This implies that ethnic divides run deep regarding the intentions to study abroad and are not mediated by the other relevant individual level characteristics (including social class/status indicators). Of the "Big Five" personality traits (Model 2), Extraversion and Openness associate positively with the probability of willingness to continue studies abroad, which is in line with previous research (Paulauskaite et al 2010, Silventoinen et al 2008. Of these two personality traits, however, only Openness remains significant after adding various forms of capital in Model 3.…”
Section: Individual-level Characteristics Shaping Intentions To Studysupporting
confidence: 87%
“…Jennings (1970) introduced the term "mobicentric man" to characterize the behaviour of individuals who value motion and action very highly and who are constantly "on the move". Recent studies have suggested that the so-called "Big Five" personality traits (Costa and McCrae 1992;Gallego and Pardos-Prado 2013;McCrae and Costa 1999)-Neuroticism, Extraversion, Openness to experience (Openness), Agreeableness, and Conscientiousness-also help to predict and explain individual mobility differences (Silventoinen et al 2008). Individuals who are more extraverted and/or more open to new experiences actively seek new opportunities which also make them more mobile (Camperio Ciani et al 2007;Jokela 2009;Paulaiskaite et al 2010).…”
Section: Abroadmentioning
confidence: 99%
“…However, such studies are not informative in evaluating whether personality influences migration or whether migration influences personality development. In a recent prospective study, Silventoinen et al (2008) found that high extraversion and neuroticism increased the probability of international migration. However, we are unaware of longitudinal studies examining whether more refined characterizations of temperament predict migration in general and selective migration to urban or rural areas in particular.…”
mentioning
confidence: 98%
“…Migration amongst elderly people takes place among those in poor health moving to avoid environmental hazards, or to be better placed to receive care (Bentham 1988). Based on an exhaustive study of Finnish twins who migrated to Sweden, Silventoinen et al (2007) identified the following risk factors for future migration: life dissatisfaction, higher alcohol abuse and smoking in both sexes, in addition to male unemployment, neuroticism and extroversion. Excessive smoking, alcohol abuse and others unhealthy behaviours may be self-selective factors of rural to urban migration.…”
Section: Discussionmentioning
confidence: 99%